Time Perception in Prodromal Alzheimer's Dementia and in Prodromal Dementia With Lewy Bodies - Pai, Ming-Chyi; Yang, Chiu-Jun; Fan, Sheng-Yu (Frontiers in Psychiatry, 2021)
Background: Time perception is a subjective experience or sense of time. Previous studies have shown that Alzheimer's disease (AD) patients have time perception deficits compared to a cognitively unimpaired control group (CU). There are only a few studies on dementia with Lewy bodies (DLB) patients’ time perception in comparison with CU and AD patients. Early intervention and prescription of the right medicine may delay the deterioration of AD and DLB, moreover, knowing how prodromal AD (prAD) and prodromal DLB’s (prDLB) time perception differ from each other might be helpful for future understanding of these two dementias. Therefore, the purpose of this study is to explore the difference in time perception performance between prodromal AD and prodromal DLB. Methods: We invited people suffering from prAD, prDLB, and CU to participate in this study. Tests of verbal estimation of time and time interval production were used to assess their time perception. We analyzed the average time estimation (ATE), absolute error score (ABS), coefficient of variance (CV), and subjective temporal unit (STU) within the three groups. Results: A total of 40 prAD, 30 prDLB, and 47 CU completed the study. In the verbal estimation test, the CV for the prAD was higher than both prDLB and CU at the 9 seconds (9s) interval, and the CV of prAD was higher than CU at the 27s interval. In the time interval production test, the subjective time units of prDLB were higher than prAD at the 10s interval, while those of both prDLB and CU were higher than prAD at the 30s interval. The percentage of subjects with STU less than 1.0s, indicating overestimation, was higher in prAD than both prDLB and CU. Conclusion: Time perception of prAD patients showed imprecision and overestimation of time, while prDLB tended to underestimate time intervals. No significant difference was found in accuracy among the three groups. It is speculated that the clinical and pathological severity of the two prodromal dementia stages may be different, and some patients have not yet had their time perception affected.